Management lessons from Mayo Clinic inside one of the world's most admired service organizations - Berry, Leonard L. 1942- (McGraw-Hill, 2008)
Management Lessons from Mayo Clinic reveals for the first time how this complex service organization fosters a culture that exceeds customer expectations and earns deep loyalty from both customers and employees. Service business authority Leonard Berry and Mayo Clinic marketing administrator Kent Seltman explain how the Clinic implements and maintains its strategy, adheres to its management system, executes its care model, and embraces new knowledge - invaluable lessons for managers and service providers of all industries. Drs. Berry and Seltman had the rare opportunity to study Mayo Clinic's service culture and systems from the inside by conducting personal interviews with leaders, clinicians, staff, and patients, as well as observing hundreds of clinician-patient interactions. The result is a book about how the Clinic's business concept produces stellar clinical results, organizational efficiency, and interpersonal service. By examining the operating principles that guide every management decision at this legendary healthcare institution, the authors are able to: (1) demonstrate how a great service brand evolves from the core values that nourish and protect it; (2) extrapolate instructive business lessons that apply outside healthcare; (3) illustrate the benefits of pooling talent and encouraging teamwork; (4) relate historical events and perspectives to the present-day Mayo Clinic; and (5) share inspiring stories from staff and patients. An innovative analysis of this exemplary institution, Management Lessons from Mayo Clinic presents a proven prescription for creating sustainable service excellence in any organization.